2017
DOI: 10.1103/physreva.96.062107
|View full text |Cite
|
Sign up to set email alerts
|

Multiparameter quantum metrology of incoherent point sources: Towards realistic superresolution

Abstract: We establish the multiparameter quantum Cramér-Rao bound for simultaneously estimating the centroid, the separation, and the relative intensities of two incoherent optical point sources using a linear imaging system. For equally bright sources, the Cramér-Rao bound is independent of the source separation, which confirms that the Rayleigh resolution limit is just an artifact of the conventional direct imaging and can be overcome with an adequate strategy. For the general case of unequally bright sources, the am… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
117
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(121 citation statements)
references
References 43 publications
(54 reference statements)
4
117
0
Order By: Relevance
“…First, we see in figure 5(a) that the error when estimating δ diverges at low separations when using either IPC or adapted SPLICE. This was to be expected since it is now known that the quantum CRB for estimating δ between unequal intensity emitters diverges at low δ [20,21]. However, we also see that the unadapted SPLICE measurement, which assumes equal intensity emitters, does surprisingly well in comparison.…”
Section: Adapting Splice For Unequal-intensity Emitterssupporting
confidence: 68%
See 1 more Smart Citation
“…First, we see in figure 5(a) that the error when estimating δ diverges at low separations when using either IPC or adapted SPLICE. This was to be expected since it is now known that the quantum CRB for estimating δ between unequal intensity emitters diverges at low δ [20,21]. However, we also see that the unadapted SPLICE measurement, which assumes equal intensity emitters, does surprisingly well in comparison.…”
Section: Adapting Splice For Unequal-intensity Emitterssupporting
confidence: 68%
“…Until recently these works have assumed the intensities of the two point sources to be equal. It has been shown [20,21] that when this assumption is relaxed-the two sources have unknown, disparate intensitiesthat the quantum Cramér-Rao bound (CRB) for an unbiased estimate of the separation diverges as separation decreases below the Rayleigh limit 5 . However, this divergence happens quadratically slower than the CRB for IPC, suggesting that measurement schemes exist which still give an advantage over directly imaging the sources.…”
Section: Introductionmentioning
confidence: 99%
“…Reháček and co-workers studied the quantum limits and the optimal measurements for two point sources with unequal brightnesses in Refs. [59,60]. They found that, while significant enhancements over direct imaging remain possible, the performance gets worse for unequal sources.…”
Section: Two Point Sources With Unequal Brightnessešmentioning
confidence: 99%
“…As shown in [4], however, the model used in [2] is not robust with respect to the inclusion of other parameters. When the intensities of the bright spots are considered as estimated parameters, together with the separation and the centroid, the QFI remains constant only if the two intensities are equal, but it drops to zero for unequal intensities.…”
Section: Introductionmentioning
confidence: 99%